Noncompaction with dysmorphism, mental retardation, general wasting, and hypogonadism requires neurologic and sophisticated cytogenetic investigations ( Author`s Reply ) - (:unkn) unknown (My University, 2015)
0
Dismorfizm, mental retardasyon, genel zayıflama ve hipogonadizm ile nonkompaksiyon nörolojik ve sofistike sitogenetik araştırmalar gerektirir
Keywords: Kalp ve Kalp Damar Sistemi